Effectiveness and safety of rivaroxaban vs. warfarin in non-valvular atrial fibrillation patients with a non-sex-related CHA2DS2-VASc score of 1. Issue 2 (17th July 2018) - Coleman, Craig I; Turpie, Alexander G G; Bunz, Thomas J; Eriksson, Daniel; Sood, Nitesh A; Baker, William L
Abstract: Aims: To compare the effectiveness and safety of standard-dose rivaroxaban (20 mg o.d.) and warfarin in non-valvular atrial fibrillation (NVAF) patients with a non-sex-related CHA2 DS2 -VASc score of 1. Methods and results: Analysis of United States Truven MarketScan claims from November 2011 to December 2016 for anticoagulant-naïve NVAF patients with a single non-sex-related stroke risk factor assigned 1-point in the CHA2 DS2 -VASc score and ≥12-months of continuous medical/prescription insurance coverage prior to the qualifying oral anticoagulant dispensing. Standard-dose rivaroxaban users were 1:1 propensity score-matched to warfarin users. Patients were followed until outcome occurrence, insurance disenrollment, or end of data availability. Primary outcomes included stroke or systemic embolism and major bleeding and were compared using Cox regression and reported as hazard ratios (HRs) with 95% confidence intervals (CIs). In all, 3319 rivaroxaban users were 1:1 propensity score-matched to 3319 warfarin users. Median (interquartile range) duration of follow-up was 1.6 (0.7, 2) years and the most common qualifying stroke risk factor was hypertension ( n = 4532, 68.3%). Rivaroxaban was associated with a significant reduction in the 1-year stroke or systemic embolism vs. warfarin (HR 0.41, 95% CI 0.17–0.98), with no significant difference in overall major bleeding (HR 0.74, 95% CI 0.44–1.26) or major bleeding subtypes (HR ranging from 0.33 to 0.78, P > 0.05 for all). Similar results were seen after extending follow-up to 2 years. Conclusions: Rivaroxaban may lower the rate of stroke or systemic embolism vs. warfarin in NVAF patients with a non-sex-related CHA2 DS2 -VASc score of 1 without impacting major bleeding.